The direct power control of three-phase AC-DC converter under unbalance voltage condition - Nor Azizah Yusoff; Azziddin M. Razali; Kasrul Abdul Karim; Auzani Jidin (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper has presents the integrated approach for three-phase PWM AC-DC converter for obtaining the symmetrical components under unbalanced supply condition. The input structures for conventional direct power control have been modified with three simpler sequence networks instead it coupled by a detailed three-phase system method. In the cases of an unbalanced three-phase system, it causes the presence of unbalanced current and voltages thus produce the negative components on the grid voltage. Otherwise, the unbalance voltage in a three-phase power system causes severe performance degradation of a grid-connected VSI. Therefore, the imbalance voltage can be resolved by separating from the individual elements of voltage and current into symmetrical components called as a sequencing network. Consequently, the input power is relatively improved during unbalanced condition. It proven through the measurement of Total Harmonic Distortion (THD) from the conventional direct power control in individual elements is much higher compared than it resolved in separate components. Therefore, three symmetrical components are necessary for imbalance supply condition to obtaining almost sinusoidal grid currents.